Entre o real e o imaginário: configurações de uma utopia feminina em A Rainha do Ignoto, de Emília Freitas - Quinhones, Elenara Walter (2015)
This research discusses the exclusion of the nineteenth century female writing from the literary field. The object of study is A Rainha do Ignoto (1899), by Emília Freitas, a novel excluded by critics because of its female authorship. Although this neglect would be explained by the assumed lack of quality of this kind of literature, it is well known that this thought reflects patriarchal ideas against women. This work was made possible thanks to previous researchers who made an archeological work and (re)discovered many female literary works which had been forsaken. The discussion of this novel begins with the consideration of feminist literary criticism in order to understand the reasons for the exclusion of writing from the literary tradition. Other excluded female literary works produced in nineteenth-century Brazil will be considered once there are basically no female literary works before the 1800 s. In the sequence, A Rainha do Ignoto will be analyzed through a feminist theoretical perspective drawn on the studies of Heloísa Buarque Hollanda (1994) and Elaine Showalter (1994). Finally, the novel A Rainha do Ignoto will be analyzed considering the context of Emília Freitas life and production, already studied by Alcilene Cavalcante s (2008). Based on the works of Raymond Trousson (1979), Carlos Eduardo Ornelas Berriel (2012), and Ana Cláudia Romano Ribeiro (2010), one may claim that Freitas novel can be considered as utopian literature of the kind produced in the western world.